STRATEGIC FINANCIAL MANAGEMENT: THE EXPERIENCE OF MULTINATIONAL COMPANIES IN THE FACE OF ASEAN ECONOMIC INTEGRATION - Mamay Komarudin; Nur Aini Firzanah Mohd Afzan (International Journal of Multidisciplinary Research and Literature, 2026)
This research aims to analyze the experience of multinational companies in implementing strategic financial management amid ASEAN economic integration. The research approach used is qualitative with multiple case study designs. Data were collected through in-depth interviews, observations, and documentation, then analyzed using NVivo to identify key themes. The results of the study show that multinational companies implement various financial strategies, such as exchange rate hedging, investment diversification, capital structure optimization, and the digitalization of the financial system, to maintain stability and increase competitiveness. ASEAN economic integration offers opportunities for market expansion, but it also poses challenges, including exchange rate fluctuations, regulatory differences, and the complexity of tax systems across countries. The company responded to these conditions by adapting through the use of local currency, regional financial centralization, and flexible financial planning. Digital transformation has also proven to be an important factor in improving the efficiency and effectiveness of financial decision-making. This study concludes that the success of multinational companies in navigating ASEAN economic integration is largely determined by their ability to implement strategic financial management that is adaptive, integrated, and digital.